THE VULKAN TECHNIQUE: A NOVEL OSTOMY-CLOSURE TECHNIQUE THAT REDUCES COMPLICATIONS AND OPERATIVE TIMES - KRENZIEN,Felix (2017)
ABSTRACT Background: Ostomy reversals remain at high risk for surgical complications. Indeed, surgical-side infections due to bacterial contamination of the stoma lead to revision surgery and prolonged hospital stay. Aim: To describe the novel vulkan technique of ostomy reversal that aims to reduce operative times, surgical complications, and readmission rates. Methods: Ostomy closure was performed using the vulkan technique in all patients. This technique consists of external intestinal closure, circular skin incision and adhesiolysis, re-anastomosis, and closure of the subcutaneous tissue in three layers, while leaving a small secondary wound through which exudative fluid can be drained. The medical records of enterostomy patients were retrospectively reviewed from our hospital database. Results: The vulkan technique was successfully performed in 35 patients mainly by resident surgeons with <5 years of experience (n=22; 62.8%). The ileostomy and colostomy closure times were 53 min (interquartile range [IQR], 41-68 min; n=22) and 136 min (IQR: 88-188 min; n=13; p<0.001), respectively. The median hospital stay was seven days (IQR: 5−14.5 days); the length of hospital stay did not differ between ileostomy and colostomy groups. Major surgical complications occurred only in patients who underwent colostomy closure following the Hartmann procedure (n=2); grade≥IIIb according Clavien-Dindo classification. Conclusion: The vulkan technique was successfully applied in all patients with very low rates of surgical-site infections. Off note, residents with limited surgical experience mainly performed the procedure while operating time was less than one hour.